The effect of financial compensation on employee performance with work motivation as a mediating variable - Putri Dwi Amanda; Okki Trinanda (Universitas Negeri Padang, 2021)
This research analyzed: (1) The effect of financial compensation on employee performance (2) The effect of financial compensation on work motivation (3) The effect of financial compensation on employee performance through work motivation. This research uses a descriptive causative method. The population in this study were employees of the Irna Anak Dr. M. Djamil Padang. The sampling technique in this study was total sampling. Data analysis was performed using SPSS software. Regarding the proposed partial mediation model, the data confirm the relationship established in the hypothesis. This study found that (1) financial compensation has a positive and significant effect on employee performance in the field of. Irna Anak, RSUP Dr. M. Djamil Padang (2) Financial compensation has a positive and significant effect on work motivation in the field of Irna Anak, RSUP Dr. M. Djamil Padang (3) Work motivation mediates the relationship between financial compensation and employee performance at Irna Anak RSUP Dr. M. Djamil Padang. The results of this study found that financial compensation is proven to have a positive and significant effect on employee performance, work motivation partially mediates the relationship between financial compensation and employee performance.